2022
DOI: 10.3390/pathogens12010064
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Genetic Diversity of Pseudomonas aeruginosa Strains Isolated from Equine and Other Veterinary Samples

Abstract: Pseudomonas aeruginosa is one of the leading causes of healthcare-associated infections in humans. This bacterium is less represented in veterinary medicine, despite causing difficult-to-treat infections due to its capacity to acquire antimicrobial resistance, produce biofilms, and persist in the environment, along with its limited number of veterinary antibiotic therapies. Here, we explored susceptibility profiles to antibiotics and to didecyldimethylammonium chloride (DDAC), a quaternary ammonium widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 81 publications
4
8
0
Order By: Relevance
“…The phenotype of DS to DDAC was also found in our veterinary study, a phenotype observed in 11.3% of the strains, mainly isolated from horses and associated with respiratory or genital type samples. In this veterinary study, the SD phenotype to DDAC was not associated with an MDR/XDR profile of the strains 25 . Interestingly, in another publication, Goodarzi et al 40 showed that out of 92 P. aeruginosa hospital strains isolated between 2019 and 2020 (Hamadan City Hospital, Iran), 32.6% had a DDAC MIC ranging from 64 to 128 mg/L as found in the present study.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…The phenotype of DS to DDAC was also found in our veterinary study, a phenotype observed in 11.3% of the strains, mainly isolated from horses and associated with respiratory or genital type samples. In this veterinary study, the SD phenotype to DDAC was not associated with an MDR/XDR profile of the strains 25 . Interestingly, in another publication, Goodarzi et al 40 showed that out of 92 P. aeruginosa hospital strains isolated between 2019 and 2020 (Hamadan City Hospital, Iran), 32.6% had a DDAC MIC ranging from 64 to 128 mg/L as found in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…However, no gene associated with the production of a carbapenemase was found to explain the resistance to carbapenems found in the animal strains. Finally, it is interesting to note that in this veterinary study, two strains were associated with ST235 25 , among the top 10 P. aeruginosa high-risk clones worldwide.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations